2021
DOI: 10.3390/app11094110
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Durability Properties of Mortars Incorporating Red Mud, Ground Granulated Blast Furnace Slag, and Electric Arc Furnace Dust

Abstract: This research studies the properties of mortars incorporating waste materials including red mud (RM), ground granulated blast furnace slag (GGBFS), and electric arc furnace dust (EAFD). Ordinary Portland cement (OPC) was partially replaced with equal contents of RM, GGBFS, and EAFD at different ratios by weight (0, 5, 10, 15, 20, 30, 40, and 50%). Slump, compressive strength, splitting tensile strength, electrical resistivity, water absorption, resistance to freeze–thaw cycles, and durability under sodium sulp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 78 publications
1
3
0
Order By: Relevance
“…12b), which further facilitated the penetration of H 2 SO 4 into the mortar's uncorroded microstructure, causing increasing damage over time [62]. These findings are in line with previous studies [66][67][68][69][70].…”
Section: H 2 So 4 Resistancesupporting
confidence: 90%
“…12b), which further facilitated the penetration of H 2 SO 4 into the mortar's uncorroded microstructure, causing increasing damage over time [62]. These findings are in line with previous studies [66][67][68][69][70].…”
Section: H 2 So 4 Resistancesupporting
confidence: 90%
“…Similar tests are not available in the literature. However, the freeze-thaw resistance was presented in [13,48,49]. The results indicated that the presence of red mud contributes to the freeze-thaw resistance.…”
Section: Freeze-thaw Resistancementioning
confidence: 92%
“…However, the fracture energy is still size dependent [20]. [39]. These material properties are shown in Table 1.…”
Section: Theoretical Review Of Size Effect Parametermentioning
confidence: 99%